Feeding ratio and frequency affects cadmium bioaccumulation in black sea bream Acanthopagrus schlegeli - Z Guo (Inter-Research, 2015)
Feeding ratio and frequency have substantial effects on food digestion and assimilation in fish, yet few attempts have been made to determine their influences on the bioaccumulation of trace metals. In this study, juvenile Acanthopagrus schlegeli were exposed to either waterborne or dietary cadmium (Cd) at different feeding ratios (0, 2, or 4% body weight d-1 [BW d-1] under waterborne Cd exposure and 1, 2.5, or 4% BW d-1 under dietary Cd exposure) or feeding frequencies (1, 2 or 8 times d-1) for 5 wk. Under waterborne Cd exposure, the fish fed 0% BW d-1 or 8 times d-1 showed significantly lower growth rates and those fed 0% BW d-1 or 1 time d-1 exhibited higher Cd body burdens and Cd uptake rates compared to the other groups. The gut showed a significantly higher waterborne Cd uptake rate than the gills when fish were fasted or fed only 1 time d-1. These results suggest that starvation and low feeding frequency facilitate waterborne Cd uptake. Under dietary Cd exposure, the fish fed 4% BW d-1 or 2 times d-1 grew faster. Cd body burden and Cd assimilation were higher in fish fed 2.5% BW d-1 or 2 times d-1. Dietary Cd retention was positively correlated with feed efficiency, suggesting the utilization of Cd probably coincides with the essential nutrients in fish. Overall, this study demonstrates that different feeding strategies significantly influence waterborne and dietary Cd bioaccumulation in marine fish. Therefore, feeding conditions have to be considered carefully for managing trace metal contamination in marine fish farming.